Vlogging and the Malaysian citizenship experience - Mohamed, Shafizan; Tengku Mohd Azzman, Tengku Siti Aisha (Aabid Raja Publisher, 2018)
This study is about examining and understanding the relationship between media and citizenship through the experiences the Malaysian vloggers. The theoretical ideas of Citizen’s Media is used to delineate and make sense of this relationship. The areas of focus are: (1) characteristics of the vloggers (2) the types of vlog, and (3) representation of citizenship. A purposive sample of 22 Malaysian vloggers was collected through a systematic process on YouTube during a three-months period. Results from the study revealed that the vloggers were young, multiracial and mostly male. While all of them talks about Malaysia or being Malaysian, there are differences in thevlogging style and stance that indicate unique representations of citizenship.